The lipid flippase SLC47A1 blocks metabolic vulnerability to ferroptosis - Lin, Zhi; Liu, Jiao; Long, Fei; Kang, Rui; Kroemer, Guido; Tang, Daolin; Yang, Minghua (Nature communications, 2022)
Ferroptosis is a type of regulated necrosis caused by unrestricted lipid peroxidation and subsequent plasma membrane rupture. However, the lipid remodeling mechanism that determines sensitivity to ferroptosis remains poorly understood. Here, we report a previously unrecognized role for the lipid flippase solute carrier family 47 member 1 (SLC47A1) as a regulator of lipid remodeling and survival during ferroptosis. Among 49 phospholipid scramblases, flippases, and floppases we analyzed, only SLC47A1 had mRNA that was selectively upregulated in multiple cancer cells exposed to ferroptotic inducers. Large-scale lipidomics and functional analyses revealed that the silencing of SLC47A1 increased RSL3- or erastin-induced ferroptosis by favoring ACSL4-SOAT1–mediated production of polyunsaturated fatty acid cholesterol esters. We identified peroxisome proliferator activated receptor alpha (PPARA) as a transcription factor that transactivates SLC47A1. The depletion of PPARA and SLC47A1 similarly sensitized cells to ferroptosis induction, whereas transfection-enforced re-expression of SLC47A1 restored resistance to ferroptosis in PPARA-deficient cells. Pharmacological or genetic blockade of the PPARA-SLC47A1 pathway increased the anticancer activity of a ferroptosis inducer in mice. These findings establish a direct molecular link between ferroptosis and lipid transporters, which may provide metabolic targets for overcoming drug resistance. Ferroptosis is cell death caused by lipid peroxidation and plasma membrane rupture. Here, the authors report an additional role for the lipid flippase SLC47A1 as a regulator of lipid remodeling and survival during ferroptosis, thereby providing a metabolic target for overcoming drug resistance.